Enhancing Soccer-Specifc Motor Skills Through Visual Training: A Quasi-Experimental Study in Young Soccer Players (Baltic Journal of Sport and Health Sciences, 2023)
In team sports like soccer, the ability to make quick decisions is essential for successful performance. Playersmust perceive and understand the available aﬀordances in their environment to eﬀectively utilize the informationand make accurate decisions on the feld. Visual exploratory actions play a crucial role in acquiring the necessaryinformation, allowing players to anticipate action possibilities and plan their subsequent actions. This study aimed toevaluate the eﬀectiveness of an innovative training protocol based on visual exercises in improving soccer-specifcmotor skills of U12 soccer players. Thirty young male soccer players participated in the study and were randomlyassigned to one of three groups: Technique Group (T-G), Visual-Technique Group (VT-G), and Control Group (C-G).The T-G received technical training, the VT-G received the same training with the addition of visual stimuli, and theC-G received regular in-season training. Pre- and post-test measurements were conducted on soccer-specifc motorskills. The results showed that the VT-G demonstrated signifcant improvements in motor skills compared to the T-Gand C-G. These fndings suggest that incorporating targeted visual training into soccer training programs can enhanceperceptual-cognitive and visual skills, leading to improved agility and overall on-feld performance.Keywords: soccer, agility, visual training, youth sports, motor skills.